Influência do alimentador de sólidos na fluidodinâmica do transporte pneumático - Lopes, Cibele Souza (Universidade Federal de São Carlos, 2007)
Pneumatic transport is an operation where powdery and granular materials are conveyed through a pipeline suspended in a gas flow. It is usually found in several industries segments and it is used as a carrier, such as, in beans production; drying operation, like grain dryers; or as reactors, in cracking catalytic reactions, combustion operations and precalciner. One of most important parts in a pneumatic conveying is the feeding system since in this area takes place an abrupt change of momentum due the introduction of solids and this influences the fluid dynamic of the system. The purpose of this wok was to carry out a study of influence of three feeders (gravity feeder, gravity feed concerted with a reduction of area and gravity feed concerted with a venturi) in the fluid dynamic of the system, identifying the main aspects of the feeders and their effects in the global system. The influence of dp and the throat diameter in the venturi feeder was evaluate. Experimental data showed that the fluid dynamic and feeding device was linked, and the shape and size of the feeder and the particle size dictated the possible operation conditions for the transport. Finally, was observed that in the literature, many authors don t consider the feeding system in their studies about pneumatic conveying. However, the results showed that special attention should be given to the feeders, since it can generate high pressure losses which increase the systems costs or even make it impracticable.
Keywords: Engenharia química fenômenos de transporte; Loop pneumático; Inserção de partículas; Comportamento fluidodinâmico; Flutuação de pressão; ENGENHARIAS::ENGENHARIA QUIMICA